Energy Consumption Connection of Industrial Sector Based on Industrial Link Theory: A Case Study of China - Xia, Jinwen; Liu, Xiaojun; Sun, Dongqi; Li, Chenxi; Wang, Zhaofei (Frontiers in Ecology and Evolution, 2022)
China's energy consumption and its growth trend not only determine the domestic energy production and supply pattern. The understanding of energy consumption and its growth changes will help to enhance urban resilience. Based on the improved input-output model and hypothetical extraction model, build energy and industry connection model with the industrial sectors of the energy industry industrial sector, relying on the multi-annual input-output table, analyze the energy transfer between industrial sectoral economic activities, and analyze the energy transfer effect between the supply side and demand side industry industrial sectors in economic activities. The results showed that, in 2017, the energy industry industrial sector was the most energy consumption industry in Shaanxi Province. The energy industrial sector belonged to the net energy output industrial sector, and the energy products transferred to other industrial sectors. This paper can provide scientific basis for the energy supply side reform and adjusting the industrial layout of regions in the Yellow River Basin.